Tanggung Jawab Guru PAK dalam Pembentukan Karakter di Era Digital - Jefrianto Gailya; Jonathan Leobisa; Yakobus Adi Saingo (International Forum of Researchers and Lecturers, 2026)
The digital era presents various opportunities as well as challenges in the world of education, particularly in the formation of student character. The development of technology, social media, and the unlimited flow of information influence the way students think, act, and behave. This condition demands the role and responsibilities of Christian Religious Education (PAK) Teachers that are increasingly complex and strategic. This study aims to describe the responsibilities of PAK Teachers in the formation of student character in the digital era. The research method used is a qualitative method with a literature study approach. Data were collected through a review of scientific journals, academic books, and theoretical sources relevant to the research topic. The results of the study indicate that PAK Teachers are not only responsible for conveying Christian faith material, but also guiding students in internalizing and practicing Christian values such as love, honesty, responsibility, self-control, and empathy, both in real life and digitally. PAK Teachers act as educators, role models, guides, and spiritual counselors who integrate character education into the learning process. In addition, PAK Teachers are required to have adequate pedagogical, professional, personality, and social competencies, as well as the ability to utilize technology wisely. Collaboration with parents and schools is a crucial aspect in sustainably shaping students' character. Thus, Christian Religious Education teachers act as agents of transformation in shaping a generation with Christian character ready to face the challenges of the digital era.